2014
DOI: 10.1016/j.clinbiomech.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ankle–foot orthosis plantarflexion stiffness on ankle and knee joint kinematics and kinetics during first and second rockers of gait in individuals with stroke

Abstract: Background Stiffness of an ankle-foot orthosis plays an important role in improving gait in patients with a history of stroke. To address this, the aim of this case series study was to determine the effect of increasing plantarflexion stiffness of an ankle-foot orthosis on the sagittal ankle and knee joint angle and moment during the first and second rockers of gait. Methods Gait data were collected in 5 subjects with stroke at a self-selected walking speed under two plantarflexion stiffness conditions (0.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…We also speculated that the increases in the flexion angles in (e) the initial knee joint angle was linked to the decreases in (f) the peak knee extension angle. These results strongly suggest that the AFOs would affect kinematics and kinetics of the knee joint in patients with stroke, and would reinforce the findings of the previous studies (Kobayashi et al, 2013; Singer et al, 2014). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We also speculated that the increases in the flexion angles in (e) the initial knee joint angle was linked to the decreases in (f) the peak knee extension angle. These results strongly suggest that the AFOs would affect kinematics and kinetics of the knee joint in patients with stroke, and would reinforce the findings of the previous studies (Kobayashi et al, 2013; Singer et al, 2014). …”
Section: Discussionsupporting
confidence: 90%
“…These results suggest an important relationship between these kinematic/kinetic parameters and the plantarflexion resistive moment of the AFO. Our previous work were either case series (Singer et al, 2014) or focused only on kinematics (Kobayashi et al, 2011a, 2013) using somewhat bulky experimental AFOs. This study is novel and important because both kinematic and kinetic parameters demonstrated statistically significant effects due to changes in the plantarflexion resistive moments using the new and compact articulated AFO in a group of 10 individuals post stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of spring-like AFOs to improve gait is however partly dependent on their stiffness. This has been shown in simulation models [ 19 ], as well as in studies in healthy adults [ 21 ] and in adult patient populations [ 23 28 ], where results indicated that changing the AFO stiffness significantly affected knee and ankle kinematics and kinetics, as well as walking energy cost. Results also indicated that the reduction in walking energy cost could be improved by choosing the appropriate AFO stiffness [ 26 ].…”
Section: Introductionmentioning
confidence: 67%
“…Differences in orthotic properties, such as ankle and footplate stiffness, footplate length and mass, may explain the variation in effectiveness (15,18). Although, these mechanical properties have been evaluated in small clinical studies of patients with lower limb salvage (19), stroke (20,21) and cerebral palsy (22), the few studies evaluating AFOs in non-spastic neuromuscular disorders did not specify the mechanical properties of the investigated AFOs (12,23). Consequently, there is a lack of evidence-based guidelines to select the most effective AFO to improve gait in this population, and choices in current practice are based on the preferences of the prescribing physician or orthotist (12).…”
mentioning
confidence: 99%